Measurement of short-range correlations in shock-compressed plastic by short-pulse x-ray scattering. - Barbrel, B; Koenig, M; Benuzzi-Mounaix, A; Brambrink, E; Brown, C; Gericke, DO; Nagler, B; Rabec le Gloahec, M; Riley, D; Spindloe, C; Vinko, S; Vorberger, J; et al. (2009)
We have performed short-pulse x-ray scattering measurements on laser-driven shock-compressed plastic samples in the warm dense matter regime, providing instantaneous snapshots of the system evolution. Time-resolved and angularly resolved scattered spectra sensitive to the correlation effects in the plasma show the appearance of short-range order within a few interionic separations. Comparison with radiation-hydrodynamic simulations indicates that the shocked plastic is compressed with a temperature of a few electron volts. These results are important for the understanding of the thermodynamic behavior of strongly correlated matter for conditions relevant to both laboratory astrophysics and inertial confinement fusion research.